Increased Neural Activity in Hazardous Drinkers During High Workload in a Visual Working Memory Task: A Preliminary Assessment Through Event-Related Potentials - Schroder, Elisa; Dousset, Clémence; Noel, Xavier; Kornreich, Charles; Campanella, Salvatore (Frontiers in Psychiatry, 2019)
Despite equated behavioral performance levels, hazardous drinkers generally exhibited increased neural activity while performing simple cognitive tasks compared to light drinkers. Here forty-nine participants (25 hazardous drinkers and 24 matched controls) were confronted to an event-related potentials (ERPs) study while performing a n-back working memory task. In the control zero-back (N0) condition, subjects were required to press a button when the number “6” was displayed. In the two-back and three-back (N2; N3) conditions, subjects had to press a button when the displayed number was identical to the number shown two/three trials before. To assess for specific working memory processes, subtractions “N2 minus N0” and “N3 minus N0” conditions were computed for light and hazardous drinkers. Three main ERP components were disclosed for both groups: a P200/N200 complex, a P300 component and a N400/P600 later activity. Results showed that, to perform the task at the same level than light drinkers, hazardous drinkers disclosed higher amplitude differences, mainly around the P300 and P600 components. These data may be considered, at the preventive level, as vulnerability factors for developing adult substance use disorders, and stressed the importance, at a clinical level, to consider such working memory processes in the management of alcohol dependence.